Model dekonstruksi bangunan berkelanjutan berbasis â€œreverse 4D BIMâ€ - Tri Joko Wahyu Adi; Novalia Andriyani (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2023)
Indonesia's increasing population and limited land have made the need for shelter, workplaces, and vertical buildings increase. As a consequence, buildings that have exceeded their service life, have changed their function, have been damaged by a disaster, and are not fit for function need to be demolished. Demolition needs special attention because the process requires complex planning, is hidden, carries high risks, and generates more than 40% of the total solid waste in developing countries. In Indonesia in particular, deconstruction has not been carried out by many demolition service providers. The government does not yet have comprehensive regulations for sustainable building demolition. This study aims to propose a sustainable demolition model by prioritizing the conservation of demolition waste material. In this study, the "reverse 4D BIM" technology is used to visualize the sequencing of the demolition process and predict the type, volume, and scheduling of disposal of demolition waste. The predicted results of demolition waste are then classified for their use using reduce, reuse, and recycle (3R) concept to maximize the sustainability of the demolition process and the circular economy. To implement this model, a 4D BIM-based building simulation is used. The simulation results show that the proposed model is effective and can be implemented for sustainable building demolition.